PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE DUA TINGGAL DUA TAMU DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 21 BATANGHARI JAMBI - eliana, Warman; Rahmi, Rahmi; Yuliana Fitri, Dewi (Pendidikan Matematika, 2014)
ABSTRACTThis research is motivated by the students during the learning activity and the lack of understanding of mathematical concepts students are still low . The study aims to determine the understanding of mathematical concepts by implementing cooperative learning model Two Stay Two Stray with LKS better than an understanding of mathematical concepts with conventional learning class VIII SMP 21 Â Batanghari Jambi and see the activities of the students during the learning of mathematics with application of cooperative learning model Two Stay Two Stray with LKS to the understanding of the concept matematis. This research is experimental , with random design on the subject . The instrument used was an essay test and observation sheets . Hypothesis testing using the U Mann-Whitney test with the MINITAB program obtained p-value = 0.000 is less than Î±, then reject H0. It can be concluded that the understanding of mathematical concepts with cooperative learning model Two Stay Two tray with LKS better than an understanding of mathematical concepts with conventional learning students with a confidence level of 95%.